The influence of the differences within the preliminary vo2max level on the Tabata training results - Kusuma, I Dewa Made Aryananda Wijaya (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
The objective of the study is to identify: (1) the influence of Tabata training from the perspective of “Good” category in preliminary VO2Max level; (2) the influence of Tabata training from the perspective of “Moderate” category in preliminary VO2Max level; (3) the influence of Tabata training from the perspective of “Poor” category in preliminary VO2Max level; and (4) the appropriate preliminary VO2Max level that should be assigned on the Tabata training method. Looking at the objective of the study, the nature of the study is indeed quantitative while the method that had been implemented is the quasi-experimental research with non-equivalent (pre-test and post-test) control group design. Within the conduct of the study, the number of the sample that had been involved was 60 respondents and these samples were gathered by means of quota sampling. Then, the data that had been gathered were analysed by using the paired sample t-test in order to test the hypotheses that had been assigned. The results of the study show that the Tabata training method is appropriate to be assigned in the “Moderate” category of preliminary VO2Max level. Departing from the conclusion, it might be implied that the study might be conducted further by adding the number of the sample and by adding the different type of samples.